Specialisation precedes diversification: R&D productivity effects - James S. Foreman-Peck; Peng Zhou (Cardiff University, Cardiff Business School, 2023)
We model how R&D enters the innovation system in four ways (intramural, extramural, cooperative, and spillover). Despite measuring three different spillovers together, for a very large sample of European enterprises we conclude that the productivity effects of spillovers were at best smaller than intramural R&D productivity effects. We also find that building on the greater skills and experience of enterprises already undertaking R&D (intensity) raised labour productivity more than providing support for those beginning R&D (extensity). Optimal extramural R&D intensity was higher than the actual level; sample firms could boost productivity either by abandoning extramural R&D or by doing much more. There were substantial differences in our sample between enterprises and countries in terms of R&D spillovers. Greater multinational corporation incidence in new EU members accounted for these countries' high direct R&D intensity productivity, regardless of their generally low overall labour productivity. Absorptive capacity made little difference to the utilisation of spillovers.
Keywords: L53; L21; H71; H25; 330; R&D; innovation; knowledge spillover